An indoor evacuation assessment algorithm for critical incident / Amir Haikal Abdul Halim - Abdul Halim, Amir Haikal (2023)
Evacuation is defined as the retreat, dispersal, or withdrawal of people from places of risk or threat. Their reception and treatment in safe environments were coordinated, controlled, and monitored. The complicated interior design of large public buildings and the involvement of many people make evacuation management more difficult. Therefore, it is essential to have the proper emergency evacuation in every high-rise building. Currently, many developed evacuation models focus on studying different evacuation behaviour and evacuation time. Hence, the models differ in terms of features. Furthermore, comparison and validation of the evacuation model is the missing process before applying the suitable evacuation model. Both procedures were made independently without any standard assessment that encapsulates the critical incident features during the indoor evacuation and virtual spatial elements.